IMPLEMENTASI SANKSI PIDANA TERHADAP PENGGUNA METHYLONE (ZAT M1) TERKAIT UNDANG – UNDANG NO 35 TAHUN 2009 - Ulfa Dewi, Debby Fitria; Oka Parwata, A A Gede (Kertha Desa; Vol. 01, No. 01, Maret 2013)
Narcotic couldn’t be regarded as a minor crime by the nation of Indonesia,because the drug has been damaging our nation with the rise of drug users in Indonesia.Drug users aren’t limited people communities, unfortunately many individual countriesmired in from they’re which is it of declared No. 35 of 2009 about narcotics with theformulation of criminal sanctions prison or death as penalty. Finaly, these things iscertainly not independent of realization of the ideal purpose of nation which has tobecome a virtous and noble character.
Keywords: Methylone, Sanction, Narcotic